Coronary Luminal Endothelial Lectinic Proteins upon Binding to N-Acetylglucosamine Become the Sensors to Flow That Induce Cardiac Paracrine-Dependent Responses - Juan Ramiro-Diaz; Alma Barajas-Espinosa; Erika Chi-Ahumada; Sandra Perez-Aguilar; David Torres-Tirado; Jesus Castillo-Hernandez; Maureen Knabb; Ana Barba de la Rosa; Rafael Rubio (New Visions in Biological Science Vol. 3, 2021)
Paracrine effectors modify parenchymal processes when coronary blood flow is applied to the endothelial lumen, although the mechanism of flow feeling is unknown. We and others have shown that oligosaccharides and lectins in the coronary endothelial luminal membrane (CELM) are involved in flow detection, and we hypothesized that cardiac effects of coronary flow are caused by a reversible flow-modulated lectin-oligosaccharide interaction. Lectins are a group of proteins widely distributed in nature that have high affinity for specific oligosaccharide sequences, a feature behind specific molecule-molecule recognitions The role of glycosylated and amiloride-sensitive Na+/Ca++ channels (ENaCs) in flow-induced endothelial responses has recently been hypothesized. Because N-acetylglucosamine (GlcNac) is a key component of glycocalyx oligosaccharides (i.e., hyaluronan (-4GlcUA\(β\)1-3GlcNAc\(β\)1-]n), the goal of this study is to isolate and characterize CELM GlcNac-binding lectins and establish their function in cardiac and vascular flow-induced effects. We created a 460-kDa GlcNac polymer (GlcNac-Pol) with excellent affinity for GlcNac-recognizing lectins for this purpose. Intracoronary treatment of GlcNac-Pol, which binds to CELM, reduces flow-dependent positive inotropic and dromotropic effects in the heart. GlcNac-Pol was also utilized as an affinity probe to isolate CELM GlcNac-Pol-recognizing lectins, yielding at least 35 lectinic peptides, one of which was the -ENaC channel. Some of these lectins may be involved in GlcNac-Pol-induced actions and flow sensing. We also used a flow-responsive and well-accepted model of endothelial-parenchymal paracrine interaction, in which isolated blood vessels were perfused at constant flow rates. We discovered that endothelial luminal membrane (ELM) bound GlcNac-Pol, nitro-L-arginine methyl ester, indomethacin, amiloride, and hyaluronidase prevent flow-induced vasodilation (FIV). Infusion of soluble hyaluronan reversed the impact of hyaluronidase. These findings suggest that GlcNac-Pol inhibits FIV by competing with intrinsic hyaluronan attached to a lectinic structure, such as the amiloride-sensitive ENaC, and displacing it. The hypothesized paracrine mediators of FIV are nitric oxide and prostaglandins.